A Comparative Study of pH Responsive Microcapsules from Different Nanocomposites. Issue 1 (25th April 2017) - Pentela, Nagaraju; Gowri A, Vijaya; Krishnamurthy, Munusamy; Boopathi, A. A; Rainu, Simran; Sampath, Srinivasan; Mandal, A. B.; Samanta, Debasis
Abstract : In the present article, we report the preparation of pH responsive microcapsules using polymethacrylic acid (PMAA) and different carbon nanomaterials, Graphene oxide (GO) or Fullerenol (FOH). The potential non-covalent interactions, as well as the comparative study in terms of stability and structural/morphological aspects of the Graphene oxide microcapsules (MGO) and fullerenol microcapsules (MFOH), were carried out using FT-IR, Raman, Thermogravimetric analysis (TGA), Differential Scanning Calorimetry (DSC) analysis, Field emission scanning electron microscopy (FESEM) and High resolution transition electron microscopy (HRTEM). The comparative drug release study for MGO and MFOH was done using UV illumination, fluorescence spectroscopy, etc. It was observed that the release of the drug (Riboflavin) at pH 4 from MGO was faster, reached the saturation point before 12 hours, as compared to that in MFOH where the saturation point was achieved after 18 hours. To the best of our knowledge, this is the first report on a comparative study of MGO and MFOH in terms of their stability, pH responsive nature, and other characteristics. This study can be utilized where the carbon nanomaterials (GO/FOH) are used in the preparation of designer microcapsules for targeted drug delivery applications since the pH varies in different parts of the human body.